2007
DOI: 10.1128/jvi.01112-07
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pseudoinfectious Yellow Fever Virus with a Two-Component Genome

Abstract: Application of genetically modified, deficient-in-replication flaviviruses that are incapable of developing productive, spreading infection is a promising means of designing safe and effective vaccines. Here we describe a two-component genome yellow fever virus (YFV) replication system in which each of the genomes encodes complete sets of nonstructural proteins that form the replication complex but expresses either only capsid or prM/E instead of the entire structural polyprotein. Upon delivery to the same cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 39 publications
(46 reference statements)
1
66
2
Order By: Relevance
“…Insertions at the N-terminal of the NS1 of flavivirus replicons are followed by 2A protease sequence of the foot and mouth disease virus (2A-FMDV) to ensure proper processing of the heterologous protein (Shustov et al 2007) or IRES-ECMV (Jones et al 2005, Ng et al 2007). All these strategies are based on standard cloning methods with the need for ligation in vitro, the use of restriction sites and a long time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Insertions at the N-terminal of the NS1 of flavivirus replicons are followed by 2A protease sequence of the foot and mouth disease virus (2A-FMDV) to ensure proper processing of the heterologous protein (Shustov et al 2007) or IRES-ECMV (Jones et al 2005, Ng et al 2007). All these strategies are based on standard cloning methods with the need for ligation in vitro, the use of restriction sites and a long time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Vero cells were infected with DENV-2 (strain New Guinea C) containing a Renilla luciferase reporter. The luciferase gene was inserted to the capsid gene of DENV-2, as previously reported (44). NITD-982 (25 nM) was added to the infected cells at various time points after infection.…”
Section: Identification Of Nitd-982mentioning
confidence: 99%
“…Thus, recombinant genomes generated by a single round of recombination between these LAV genomes and WT genetic material would not be viable. Recently, we showed that flaviviruses can replicate as two-component genome viruses, a system that opens up the opportunity of producing a new class of LAV (39). However, large-scale production of these viruses in vitro requires coinfection of two defective genomes in the same cell, providing a situation that could result in intergenomic recombination leading to the production of replication-competent viruses that could be pathogenic.…”
mentioning
confidence: 99%